Trace : Works on Paper. - Gallery Moving Space, Gent (Gent : Gallery Moving Space, 1990)
Croquant, Philippe ; Gijzen, Jac ; Kane, Ian ; Migliore, Bartolomeo ; 't Kindt, Jacques ; Van Den Akker, Peter
Trace : Works on Paper, Gallery Moving Space, Gent, 08.09.1990 - 07.10.1990
boek